Higher Education in South Africa A Scholarly Look Behind the Scenes. - Bitzer, Eli (Research into Higher Education Ser., 2009)
""Higher Education in South Africa should be of considerable interest to higher education researchers outside of South Africa, as well as within, for the general and comparative assessments it makes.